Prohibition of Interfaith Marriage in Indonesia: A Study of Constitutional Court Decision Number 24/PUU-XX/2022 - Imaro Sidqi; Mhd. Rasidin (IAIN Manado, 2023)
This article aims to analyze the decision of the Constitutional Court Number 24/PUU-XX/2022 concerning interfaith marriage from a philosophical, juridical, and empirical-sociological perspective so that it is more comprehensive because it covers various aspects, including religious views, law, interreligious communication, change law, human rights perspective, and polemic in society. This research is juridical-normative research, which uses a statutory approach, a concept approach, and a case approach through descriptive-qualitative analysis. The study results show that interfaith marriages are not permitted in Indonesia, both from the point of view of Islamic Law, the laws of other religions, the sociocultural community, and the Marriage Law. Therefore, the Constitutional Court issued several decisions to prohibit interfaith marriages, one of which was the Constitutional Court Decision Number 24/PUU-XX/2022, which completely rejected interfaith marriages. In its decision, the Constitutional Court does not allow interfaith marriages for three simple reasons: First, philosophically, interfaith marriages do not represent Pancasila and the essence of the formation of the Constitution. Second, juridically, interfaith marriages have no place in the Marriage Law because the state protects religion, so society remains following its corridors. Third, sociologically, interfaith marriage violates many norms, both local religion and custom. Therefore, from the perspective of religion, law, and sociocultural norms, interfaith marriages are generally not permitted in Indonesia so this research can formulate a balanced policy between individual rights and religious values in interfaith marriages.